BACK VOWEL INTERFERENCE OF MADURESE TO ENGLISH LANGUAGE PRONOUNCIATION: INTERFERENSI BUNYI VOKAL BELAKANG BAHASA MADURA PADA PELAFALAN BAHASA INGGRIS - Wilda Fizriyani; Nadzirul Mujtaba; Mufadila Fibiani; Ika Nurhayani (LLDIKTI Wilayah X, 2023)
The study discusses the differences of back vowel systems of Madurese and English, the pronunciation of English back vowels uttered by Madurese native speakers through the measurement of F1 and F2 using PRAAT, and examines the types and causes of interferences. The research is qualitative. The data are the recorded pronunciation of five Madurese junior students of English Education Students of Teaching and Education Faculty of Islamic University of Malang (UNISMA) who live in Malang. The data was collected by using elicity technique and analyzed using Miles and Huberman's analytical model. The results showed that the back vowel /u/ pronounced by Madurese Native Speakers is similar to the sound /ʊ/. A similar condition occurs when Madurese Native Speakers pronounce the sounds /ɔ/ and /ɒ/, where the quality of formant measurement vowel /ɒ/ closes to vowel /ɔ/. Meanwhile, the formant value for the pronunciation of vowel /o/ is relatively stable and almost as good as English Native Speaker pronunciation. The type of interference occurs is substitution interference. It happens because of the first language phonological rules are still used when they utter the second language and the lack of English vocabularies owned by Non Native English speaker influences the pronunciation of some phoneme in second language.